Spontaneous coronary artery dissection in the postpartum period: association with antiphospholipid antibody. Issue 9 (13th August 2004) - Krishnamurthy, M; Desai, R; Patel, H
Abstract : Spontaneous coronary artery dissection (SCAD) is an extremely uncommon cause of myocardial infarction, occurring predominantly in women during or after pregnancy. The exact aetiology is unknown. This report describes a 33 year postpartum woman with diagnosed SCAD who tested positive for anticardiolipin antibody. This is the first case of SCAD in a patient with antiphospholipid antibody. The authors hypothesised that there should be a strong association between them.